MANAJEMEN WAKTU DI USIA MADYA UNTUK MEMINIMALISIR DAMPAK DARIEMPTY NEST SYNDROME - Jamaludin Ghafur (Asian Journal of Innovation and Entrepreneurship, 2014)
Middle age called "family cycle phase sags" in married life, because the mostimportant change during this period aided by the reduction in the number of familymembers living at home. Middle age is also called the period of "empty nest". Empty nestperiod called the Empty Nest Syndrome. Empty nest syndrome is a marital satisfactionwould decline because the parents get a lot of satisfaction from his children, andtherefore, the departure of the child from the family will leave parents with an emptyfeeling. Lilian in his study of American women found that women who only perform itstraditional tasks exclusively in the home and do not have other activities outside thehome, suffered more severe syndrome, even to the level of depression as "a sense of nolonger needed" that is so concentrated. Therefore, it is important for people of middleage determine the impact of Empty Nest Syndrome and how to minimize the impact ofEmpty Nest Syndrome. There are some good ways to overcome the adverse EmptyNest Syndrome, one with an adjustment to the family which in this case means thespouse or husband.